2013
DOI: 10.1212/wnl.0b013e318296e917
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 antibody–negative neuromyelitis optica

Abstract: This raises the question of a distinct physiopathology for patients with AQP4-Ab-negative NMO and of their place in the spectrum of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
142
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 35 publications
9
142
0
Order By: Relevance
“…We believe that this fact may be due to a selection bias, overestimating those cases where CNS inflammatory disease was suspected but did not match MS criteria, such as recurrent optic neuritis or idiopathic LETM. Taking into account the comparison between AQP4-IgG seropositive and seronegative patients, we found a higher proportion of females among the positive ones, similarly to what have been previously reported [24]. Analysing the group of AQP4-IgG seropositive patients, we found similar clinical characteristics to what have been reported in the UK and Japan cohorts [25], including mean age at onset, percentage of female patients, disease course and form of presentation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We believe that this fact may be due to a selection bias, overestimating those cases where CNS inflammatory disease was suspected but did not match MS criteria, such as recurrent optic neuritis or idiopathic LETM. Taking into account the comparison between AQP4-IgG seropositive and seronegative patients, we found a higher proportion of females among the positive ones, similarly to what have been previously reported [24]. Analysing the group of AQP4-IgG seropositive patients, we found similar clinical characteristics to what have been reported in the UK and Japan cohorts [25], including mean age at onset, percentage of female patients, disease course and form of presentation.…”
Section: Discussionsupporting
confidence: 88%
“…The mortality rate was 8.3% in our cohort, higher than the Japanese but lower than the UK cohorts [25]. In fact, recent studies comparing seropositive and seronegative patients brought new concepts, including switching the NMO definition from a clinical phenotype to a biological one [24].…”
Section: Discussionmentioning
confidence: 58%
“…This is in keeping with recent findings and contrasts with AQP4 antibody-positive patients, who are more likely to be non-Caucasian. 7,8 A recent report of 16 MOG antibody-positive patients of a similar median age found that most patients were male. 24 We did not find a statistically significant association with sex, age at onset, and MOG antibody status.…”
mentioning
confidence: 98%
“…Also, cases of sero-negative NMO are quite different from those of sero-positive NMO as they present with concurrent acute myelitis and optic nerve involvement with mono-phasic presentation and lesser female preponderance [5]. Nevertheless it's important to have an early diagnosis and differentiation from MS, more so because of the high incidence of relapse in NMO and even deterioration in NMO in response to MS modifying treatment [6].…”
Section: Introductionmentioning
confidence: 99%